1990
DOI: 10.1007/bf00216925
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxine therapy for palmar-plantar erythrodysesthesia associated with continuous 5-fluorouracil infusion

Abstract: The limiting toxicity of low dose continuous infusion 5-fluorouracil (200-300 mg/m2/day) is often palmar-plantar erythrodysesthesia (PPE). PPE developed in 16/25 patients (exact 95% confidence interval of 42%-82%) with metastatic colon cancer enrolled in a phase II trial. In this trial, 5-FU was given continuously at a dose of 200 mg/m2/day until toxicity or progressive disease forced discontinuation. The first signs of the syndrome developed at a median of 2 months following infusion initiation and, unless tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(59 citation statements)
references
References 19 publications
1
57
1
Order By: Relevance
“…In seven (27%) patients, somnolence grade 1 was observed. Skin toxicity, particularly hand-foot syndrome, was seen in 15 patients (58%); however, in only one patient at the dose level of 125 mg/m 2 did hand and foot syndrome toxicity exceed grade 2 resulting in a dose reduction of 5-FU/LV and cotreatment with pyridoxine (19). Only one patient at the dose level of 125 mg/m 2 did have one episode of neutropenic sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…In seven (27%) patients, somnolence grade 1 was observed. Skin toxicity, particularly hand-foot syndrome, was seen in 15 patients (58%); however, in only one patient at the dose level of 125 mg/m 2 did hand and foot syndrome toxicity exceed grade 2 resulting in a dose reduction of 5-FU/LV and cotreatment with pyridoxine (19). Only one patient at the dose level of 125 mg/m 2 did have one episode of neutropenic sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…Topical corticosteroids have an effective role in the management of symptoms however these may also cause thinning of the skin (Komamura et al, 1995;Vakalis et al, 1998), which was observed in some female patients in our study. The patients were also prescribed with Vitamin B6, which is known to be highly effective in both the prophylaxis and control of symptoms (Fabian et al, 1990). Other than HFS, there were no other symptoms of grade 3 in the patients of FOLFOX 4 pertaining to skin and subcutaneous toxicity (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…Palmar-plantar erythrodysthesia, a potential complication of infusional 5-fluorouracil therapy, was treated with pyridoxine 50 mg t.i.d., p.o. (Fabian et al, 1990). The infusion was continued until disease progression or 24 weeks of treatment had been completed.…”
Section: Treatmentmentioning
confidence: 99%